Generation of site-specific ubiquitinated histones through chemical ligation to probe the specificities of histone deubiquitinases - AlAfaleq, Nouf Omar; Choi, Yun-Seok; Atanassov, Boyko S.; Cohen, Robert E.; Yao, Tingting (Frontiers in Epigenetics and Epigenomics, 2023)
The attachment of mono-ubiquitin to histones as a post-translational modification plays important roles in regulating chromatin structure and function. Like other epigenetic modifications, the site of ubiquitin attachment is critically important in determining its functional outcome. Depending on the type of histone and the specific lysine residue that is modified, ubiquitination acts in diverse pathways including DNA damage repair, transcription elongation, and transcription repression. Specific reader, writer and eraser activities have evolved to distinguish nucleosomes by ubiquitination of different sites. To facilitate biochemical studies of ubiquitinated nucleosomes, we have developed an efficient strategy to chemically ligate intact ubiquitin and histone proteins at specific sites to generate near-native ubiquitin-histone conjugates. Because these chemically-ligated ubiquitin conjugates are hydrolysable, they enabled us to characterize in vitro the specificities of several histone deubiquitinases. To gain insight into the mechanisms that contribute to the specificities of these deubiquitinases, we used a free Ub sensor-based real-time assay to determine their Michaelis-Menten kinetics. Our results confirmed previously reported specificities of BAP1 and USP22, but also revealed specificities of other histone deubiquitinases that have been less well defined in the literature.